2018
DOI: 10.1172/jci.insight.122572
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and maternal obesity are associated with epigenome-wide methylation changes in children

Abstract: Offspring of women with gestational diabetes mellitus (GDM) are at increased risk of developing metabolic disease, potentially mediated by epigenetic mechanisms. We recruited 608 GDM and 626 control offspring from the Danish National Birth Cohort, aged between 9 and 16 years. DNA methylation profiles were measured in peripheral blood of 93 GDM offspring and 95 controls using the Illumina HumanMethylation450 BeadChip. Pyrosequencing was performed for validation/replication of putative GDM-associated, differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 53 publications
3
86
4
1
Order By: Relevance
“…The PACE consortium identified that the majority (72 out of 86) of CpG sites that were differentially methylated at birth persist in adolescence [42]. Despite the evidence for high maintenance of DNA methylation across life, we did not see any overlap in DNA methylation changes comparing our data from GDM newborns and individuals at 12 years of age from another study [43]. As discussed above, this discrepancy could be caused by cell type specificity or technical bias.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The PACE consortium identified that the majority (72 out of 86) of CpG sites that were differentially methylated at birth persist in adolescence [42]. Despite the evidence for high maintenance of DNA methylation across life, we did not see any overlap in DNA methylation changes comparing our data from GDM newborns and individuals at 12 years of age from another study [43]. As discussed above, this discrepancy could be caused by cell type specificity or technical bias.…”
Section: Discussioncontrasting
confidence: 51%
“…Given that the epigenome is amenable to environmental factors, all the epigenetic marks that we detected in newborns may not be stable throughout life and therefore, may not have any physiological or pathological effect. The notion that most DNA methylation marks are maintained throughout life is suggested by several studies, notably studies investigating DNA methylation signatures in obesity and GDM and which showed that epigenetic signatures detected at birth persist in adolescence [42,43]. The PACE consortium identified that the majority (72 out of 86) of CpG sites that were differentially methylated at birth persist in adolescence [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, maternal obesity can lead to DNA methylation changes, which are present at birth and remain postnatally. In fact, the study of maternal obesity, with or without GDM, has shown many differentially methylated sites in DNA from the umbilical cord blood of offspring, and from 4-5 year-olds and 9-16 year-olds [39,40].…”
Section: Epigenetics Diet and Human Healthmentioning
confidence: 99%
“…As for the diet, animal model research has identified tissue-level epigenetic alterations in the fat, muscle, pancreas and liver biopsies from the offspring of mothers fed with specific diets [70][71][72][73][74]. On the other hand, due to ethical and clinical limitations, most human studies have examined epigenetic profiles mainly in placenta, offspring umbilical cord or infant blood as surrogate markers of metabolic tissue-level epigenetic modifications [39,40,[75][76][77][78][79]. The vast majority of these studies have focused on DNA methylation, while miRNA expression and histone modifications need to be better understood.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Также мы хотели бы обратить внимание на то, что причиной развития ЗВУРТ у детей, рожденных от матерей с СД-1, могут быть изменения в ткани плаценты. Подтверждение своего мнения мы нашли в работе Р. М. Есаян [55]. Клиницист при микроскопическом изучении плацент, полученных от женщин с СД 1 типа, обнаружила признаки ее поражения: несоответствие зрелости ворсин плаценты сроку гестации; признаки преобладания процессов разветвленного ангиогенеза; утолщение синцитио-капиллярных мембран; незрелость вновь образованных сосудов в ворсинах плаценты; низкую степень васкуляризации ворсин; активацию экспрессии VEGF 1,2 и 3 типов эндотелия сосудов ворсин плаценты.…”
Section: таблицаunclassified